Nutritional status of third trimester pregnant women correlates positively with birth weight - Ratna Ernawati; Bangun Trapsila Purwaka; Budi Prasetyo (Universitas Airlangga, 2017)
Objectives: to identify correlation between nutritional status (energy, macronutrient and fluid intake) of the third trimester pregnant women and birth weight.Materials and Methods: correlative analytic prospective cohort’s study in Public Health Center Jagir, Surabaya with sample comprising healthy pregnant women aged 20-35 years in the third trimester and their newborns (n=34). Respondents noted fluid intake every day for 7 days (record method) and food for 24 hours (recall method). Adequacy of energy intake, macronutrient and fluid (mean) was assessed based on AKG 2012. LBW when <2500 g. Statistical analysis used Pearson correlation's and Spearman's rho with test with significance level of p<0.05.Results: in third trimester pregnant women energy intake (r: 0.854, p: 0.0001) and carbohydrates (r:0.912, p:0.0001) had strong positive correlation, protein intake had moderate positive correlation (r: 0.519, p: 0.0001), fat intake (r: 0.425p: 0.012) and fluid (r: 0.469 p: 0.005) had positive correlation with birth weight. The prevalence of LBW in Public Health Center Jagir Surabaya was 14.7%.Conclusion: Nutritional status of third trimester pregnant women correlates positively with birth weight.